Luminance noise impacts putative luminance components of visual evoked potentials but not chromatic components - Bellany Barbosa Lopes; Terezinha Medeiros Gonçalves Loureiro; Felipe André da Costa Brito; Letícia Miquilini; Alódia Brasil; Marcelo Fernandes Costa; Railson Cruz Salomão; Dora Fix Ventura; Ana Leda Brino; Givago da Silva Souza (Psicologia: Reflexão e Crítica)
Abstract Introduction Pseudoisochromatic stimuli are widely used in psychophysical color vision testing and the features of the luminance noise present on these stimuli have been reported modifying the psychophysical chromatic discrimination. Objective The present study investigated how modifications in the luminance noise features (luminance contrast and number of luminance values) affect chromatic visual evoked cortical potentials (VECP) elicited by pseudoisochromatic gratings, aiming to evaluate the influence of luminance contrast and the number of luminance values in the pseudoisochromatic stimulus on the chromatic VECP. Methods The sample consisted of seven young trichromatic participants. The waveforms of the visual evoked cortical potentials (VECP) were analyzed, focusing on the P1, N1, and P2 components across all stimulus conditions. The luminance noise contrast in the pseudoisochromatic stimulus had distinct effects on the amplitudes of the VECP components. Significant effects were observed for the amplitudes of the P1 (p = 0.01) and P2 (p = 0.04) components, while no significant effect was found on the amplitude of the N1 component (p = 0.3). Results There was no significant effect of the luminance noise range on the latency of the VECP components (P1 VECP component, p = 0.54; N1 VECP component, p = 0.79; P2 VECP component, p = 0.49). The number of luminance values in the noise had no significant effect on VECP components amplitude and latency. Different manipulations of luminance noise influenced P1 and P2 VECP components and no modification of the luminance noise had influence on the main chromatic VECP component, N1 component. Conclusion Manipulations in features of the luminance noise in pseudoisocrhomatic stimulus impacted in putative luminance components, but not chromatic components, of visual evoked potentials. The present findings may have potential applications in clinical neuro-ophthalmology, particularly for assessing congenital and acquired color blindness.